KEBIJAKAN KOTA LAYAK ANAK: PROGRAM RUMAH PINTAR SEBAGAI RUANG PUBLIK UNTUK PEMANFAATAN WAKTU LUANG - novita, dila (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2019)
Child Friendly City is a program that aims to create an environment that can fulfill children's rights. One of the children's rights that must be given is the use of leisure time by providing public spaces that can be accessed by all children. The city of Bekasi is one of the cities that strives to create a Child-Friendly City, the commitment contained in the Regional Regulation of Bekasi City No. 13 of 2017. One of the efforts of the Bekasi City Government in fulfilling children's rights related to the utilization of leisure time by forming the Smart House Program. This study aims to analyze the Child Friendly City Policy in the City of Bekasi in the implementation of the Smart House Program as a public space for leisure time utilization. In this study a monitoring and evaluation process was carried out on the implementation of the Smart House Program in two sub-districts namely South Bekasi District and East Bekasi District. The paradigm used is constructivism with qualitative research methods. Data collection techniques by conducting direct observation, in-depth interviews and literature studies. The informant recruitment technique used was purposive sampling and snowball sampling. The results of this study state that the implementation of the Smart House Program as the provision of public space in the utilization of leisure time in both sub-districts is still not optimal, so that the impact felt by children is less significant. This is because some centers do not work in these two Smart Houses, children can only take advantage of facilities located on the outside of the Smart House such as: play facilities, pavilion and field.